PHENOMENON OF CORPOREALITY IN UKRAINIAN MODERN NOVELS - Byshenko, Tetiana (Літературний процес: методологія, імена, тенденції, 2019)
This research is devoted to the theoretical basement of the practical analysis of body and corporeality in the texts. The analysis of the body in the artistic text is based on its semantic and structural influence, which makes it possible to consider its text-creating function as an important factor in the formation of a modern novel. Body and corporeality are the factors which create a figurative and narrative component of text, and through them completely new artistic category is synthesized. Considering the body as a factor in creating a text is possible with an anthropological, cultural and literary model, through the prism of physical-mimetic analysis, gender studies and moduses of perception. Body is a method of interpretation of the surrounding world, this is a reason why it is studied by literary scholars in corporeality, sexuality, gender aspects, and traumatic experience (war, torture, injure). It is necessary to distinguish the categories of «body», «corporeality» to maintain the clarity of interpretation, thus retaining the duality between the biological and spiritual beings. The analysis demonstrates theoretical features of these categories on the researches of Ukrainian and foreign literary critics. The transformation of the image of corporeality in modern Ukrainian literature is demonstrated on the novels written by L. Dashvar, M. Matias, Yu. Wynnychuk and V. Lys. The proposed model for analyzing artistic text is universal, and can be actively used to interpret novels, in which the body acts as a narrator, regardless of whether the novel itself is an erotic. DOI: https://doi.org/10.28925/2412-2475.2019.1312